(Extra)Ordinary Presence Social Configurations and Cultural Repertoires - Paul, Heike 1968-; Kirchmann, Kay 1961-; Gottwald, Markus 1974- (Präsenz und implizites Wissen, 2017)
Taking its cue from contemporary western debates on presence in the social sciences and the humanities, this volume focuses on 'presence' both as everyday experience and as an experience of intense moments. It raises questions about diverse social configurations of presence as well as about the specific cultural repertoires which encode, articulate, and shape discourses of presence. The contributions take as a premise that phenomena of presence are connected to particular forms of knowledge. Especially tacit knowledge (pre)determines experiences of individual and collective presence and becomes tangible in moments of presence or presentification